ANALISIS KEBIJAKAN DAN IDENTIFIKASI PRIORITAS PENGEMBANGAN ANGKUTAN LAUT DI KABUPATEN KEPULAUAN MENTAWAI - , Gusri Ramayana Mila Sari, Gumilang Aryo Sahadewo, S.E., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Mentawai Islands Regency, as an archipelago that uses marine transport as the main transportation requires a development policy of reliable ocean freight to meet the needs of society and accelerate the movement of economic growth. This policy analysis and identification of priorities on the development marine transportation research aims to identify the general policy of marine transportation in Mentawai Islands